Social protection strategies in response to crises the Philippine experience - Almazan, Rainier V.; Hega, Mylene D.; Ofreneo, Rosalinda Pineda (2012)
This article explains how the Philippine financial, economic and environmental crises provided the impetus for the development and refinement of an operational framework on social protection for the country. It defines and and identifies risks as well as the corresponding social protection responses to these risks. After discussing the official Philippine definite main elements and ion of social protection as well as its key components, it traces the evolution of the enhanced social protection operational framework, together with its main elements and implementing strategies. It focuses on the National Household Targeting System for Poverty Reduction (NHTS-PR) as a new a major element and on convergence and building adaptive capacity as innovative and potentially transformative strategies in the era of climate change. It critiques the inadequate and disproportionate financing of social protection programs, as well as the conventional criteria for assessing them. Taking off from the human rights-based social protection floor advocated by the ILO and other UN agencies, it argues for transparent and participatory processes of monitoring and evaluation and recommends the broad perspective of sustainable human development to inform not only social protection butalso broader poverty reduction strategied
Keywords: Social protection